Application of the general message of balanced nutrition during the pandemic coronavirus disease 2019 (COVID-19) in Mataram City - Luh Putu Prema Wadhani; Nani Ratnaningsih (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Coronavirus Disease 2019 (COVID-19) in 2020 became the limelight worldwide, including in Indonesia. Infection caused by this virus can be prevented by social distancing, physical distancing, and a healthy lifestyle. Maintaining nutritional intake by implementing balanced nutrition guidelines is very important to enhance the immune system.Objectives: This study aimed to determine the description of the application of balanced nutrition guidelines during the COVID-19 pandemic in the community in Mataram City.Materials and Methods: This research was a descriptive study with a survey approach, and the data taken were cross-sectional. This research was conducted in May-June 2020 in the community in the Mataram City taken by purposive sampling with inclusion criteria, namely women and men of productive age, domiciled in the city of Mataram, married status, and at least elementary school education. Respondents in this study were 460 respondents who were calculated using the Slovin formula. Data on the application of balanced nutrition guidelines were obtained using a questionnaire. Data from the results of this research were analyzed using descriptive methods.Results: There are as many as >90% of the community has implemented a general message of balanced nutrition in addition to the fifth message. As many as 89.9% of respondents did not apply the fifth general message of balanced nutrition in limiting consumption of sweet, salty, and fatty foods. The majority of applications >50% of general messages of balanced nutrition were applied by respondents aged 21-29 years, female, high education and work status. Conclusions: The application of the general message of balanced nutrition during the epidemic COVID-19 in Mataram City was implemented optimally, but this application was not carried out in the fifth message in limiting consumption of sweet, salty, and fatty foods.